All‐MXene Cotton‐Based Supercapacitor‐Powered Human Body Thermal Management System. Issue 4 (19th January 2021) - Li, Jianmin; Chen, Jianmei; Wang, Hao; Xiao, Xu
Abstract: Invited for this month's cover picture is the group of Prof. Xu Xiao at the University of Electronic Science and Technology of China. The cover picture shows a little boy who is celebrating Chinese New Year outdoors with his dog. To keep warm, he is wearing a MXene‐cotton‐based human body thermal management textile, which is also powered by MXene‐cotton‐based supercapacitors. Read the full text of the Article at 10.1002/celc.202001536 . Abstract : "MXene‐coated cotton fabric (MCF), with high conductivity, good stability and washability, as well as excellent water vapor permeability and air permeability, is fabricated and is promising when used as a joule heater for personal body thermal management (PBTM) and as an electrode for supercapacitors. A wearable supercapacitor‐powered PBTM system is established by using the as prepared MCF, showing superior potential toward wearable electronics … " Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Article at 10.1002/celc.202001536 .